AID FROM THE SPECIAL FUND FOR EXPORT PROMOTION: DIFFERENCE BETWEEN FORECASTS AND ACTUAL RESULTS (2015-2017) (مجلة الواحات للبحوث والدراسات, 2023)
Abstract: Since the beginning of 2000, Algeria has adopted policies to encourage non-hydrocarbon exports subject to aid granted to exporters by the FSPE. This paper shows that there is a considerable gap between the funds consumed by the FSPE in official statistics and the ones that would have been spent if these funds had been properly used in the period 2015 to 2017. A hypothesis is put forward to explain this discrepancy, which consists in stating that the performance of the reimbursement process for this type of incentive and support has been poor.KEYWORDS: Estimate of FSPE expenditure, Export promotion, Foreign Trade Policy, Special Export Promotion Fund.